Binding of human immunodeficiency virus type 1 (HIV-1) RNA to recombinant HIV-1 gag polyprotein. - Luban, J (1991)
We have expressed the human immunodeficiency virus type 1 (HIV-1) gag polyprotein (Pr55gag) in bacteria under the control of the T7 phage gene 10 promoter. When the gene encoding the viral protease is included in cis, in the -1 reading frame, the expected proteolytic cleavage products MA and CA are produced. Disruption of the protease-coding sequence prevents proteolytic processing, and full-length polyprotein is produced. Pr55gag, separated from bacterial proteins by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) and immobilized on nitrocellulose membranes, binds RNA containing sequences from the 5' end of the HIV-1 genome. This binding is tolerant of a wide range of pH and temperature but has distinct salt preferences. Conditions were identified which prevented nonspecific binding of RNA to bacterial proteins but still allowed binding to Pr55gag. Under these conditions, irrelevant RNA probes lacking HIV-1 sequences bound Pr55gag less efficiently. Quantitation of binding to Pr55gag by HIV-1 RNA probes with deletions mutations demonstrated that there are two regions lying within the HIV-1 gag gene which independently promote binding of RNA to Pr55gag.